Ovarian Cyst Formation Following Gonadotropin-Releasing Hormone-Agonist Administration Decreases the Oocyte Quality in IVF Cycles - Muammer Doğan; Sevtap Hamdemir; Fatma Nur Aksakal; Esma Sarıkaya; Özlem Gün Eryılmaz; Leyla Mollamahmutoğlu (Balkan Medical Journal, 2012)
Objective: The gonadotropin-releasing hormone-agonist (GnRH-a) treatment during in vitro fertilization (IVF) sometimes causes a functional ovarian cyst during the administration period before gonadotropin stimulation, as an undesired event. The aim of this study was to analyze the effect of these cysts on the IVF outcomes.Materials and Methods: Out of 981 IVF cycles, 78 with ovarian cysts were retrospectively analyzed with respect to the demographic characteristics, hormonal outcomes, and fertilization, implantation and clinical pregnancy rates. Results: The metaphase II oocyte ratio, fertilization rate and percentage of high quality embryos (grade 1) were significantly higher in the cyst-negative group (p<0.0001; p<0.0001; p≤0.05). These same three parameters were also significantly higher in the cyst-aspirated group (p<0.01; p<0.05; p<0.05). Cyst diameters of the aspiration group were significantly higher (p<0.05). No statistically significant differences in implantation and clinical pregnancy rates were determined between the groups.Conclusion: An ovarian cyst formation during the GnRH-a suppression period negatively affects oocyte quality. Cyst aspiration before gonadotropin stimulation does not improve the IVF outcome.